STRATEGI INFLUENCER MARKETING SEBAGAI UPAYA OPTIMALISASI BRAND AWARENESS DAN MINAT BELI KONSUMEN WARDAH - Salsabila Imarotul Maftuhah; Mustofa (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study explains whether influencer marketing can be used as the most effective brand awareness strategy in increasing consumer interest in Wardah products. This research uses a qualitative method with a library research approach taken from scientific articles and scientific journals about Halal cosmetics and skincare in Indonesia. The results of the study show that influencer marketing can increase brand awareness through several mechanisms, namely influencer credibility, authenticity of content, visual appeal, and influencer informative that attracts consumer buying interest. This study found that Wardah brands in their Wardah products need to choose credible influencers, provide educational content in marketing Wardah products.